2015
DOI: 10.1021/acsmedchemlett.5b00433
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Staphylococcal Biofilm Effects of Human Cathelicidin Peptides

Abstract: Staphylococcus aureus can live together in the form of biofilms to avoid elimination by the host. Thus, a useful strategy to counteract bacterial biofilms is to re-engineer human antimicrobial peptide LL-37 so that it can be used as a remedy for preventing and removing biofilms. This study reports antibiofilm effects of four human cathelicidin LL-37 peptides against community-associated and hospital isolated methicillin-resistant Staphylococcus aureus (MRSA) strains. Although the intact molecule LL-37 inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 33 publications
3
101
0
2
Order By: Relevance
“…stuartii growth (Fig 1A). Data show that Omp-Pst2 is involved in pH regulation (Fig 4G) and could be in charge of ammonium clearance/neutralization from/in the periplasm, a hypothesis supported by electrophysiology data [40] and more recently molecular dynamics simulations on the porin [42]. Our data add to the growing body of evidence that suggests an implication of OM components in biofilm formation and regulation [48,49].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…stuartii growth (Fig 1A). Data show that Omp-Pst2 is involved in pH regulation (Fig 4G) and could be in charge of ammonium clearance/neutralization from/in the periplasm, a hypothesis supported by electrophysiology data [40] and more recently molecular dynamics simulations on the porin [42]. Our data add to the growing body of evidence that suggests an implication of OM components in biofilm formation and regulation [48,49].…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, MD simulations have suggested that Omp-Pst2 could be involved in the facilitated transport of cations from the periplasm to the extracellular side of the OM [42]. They furthermore highlighted that Omp-Pst2 channel would respond by gating to a massive transit of cations from the external medium to the periplasm [42]. Thus, we favour the hypothesis that Omp-Pst2 alleviates the toxic effects of urea on P .…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…For instance, merecidin (formerly known as 17BIPHE2), a human LL-37 derived peptide, can disrupt the biofilms of S. aureus USA300 under laboratory conditions [65], but is unable to do so in the case of P. aeruginosa . This may result from the complex nature of biofilms with a protective biopolymer coating for the bacterial communities.…”
Section: Application Strategies Of Antimicrobial Peptidesmentioning
confidence: 99%